An investigation of the corporate responsibility report assurance statements of the Big Four banks in Australia - Choon-Yin Sam; Paul N. C. Tiong (Journal of Economics Library, 2015)
The corporate responsibility report demonstrates an organisation's commitment to sustainability. Currently, not much is known about the quality of the assurance statements of the corporate responsibility reports of banks in Australia. This research study fills the gap in the literature by investigating the corporate responsibility report assurance statements of the Big Four banks in Australia. The assurance statements are evaluated against the criteria provided by O'Dwyer and Owen (2005) and Perego and Kolk (2012). The results reveal that although the assurance statements, on average, meet the criteria highly, there are areas that need improvement.
Keywords: G21; M14; M41; 330; assurance; bank; AA1000AS; ASAE 3000; ISAE 3000